(untitled) (Damascus University Journal of agriculture sciences, 2024)
The introduced and locally cultivated hybrids of tomatoes have many important traits comparing to other genotypes. These hybrids are characterized by their abundant yield and high fruit quality, in addition to their tolerance of many diseases. Therefore, this study aimed to evaluate the genetic diversity of eight locally cultivated tomato hybrids. The ISSR technique was used using 20 primers, all of them gave bands of DNA in the studied hybrids, the total number of amplified bands reached 193, including 157 polymorphic bands with a polymorphism average of 79.65%. The number of total bands per primer ranged from 2 to 20 with an average of 9.65. The average value of PIC was 0.34. The highest PIC value was 0.5 for P1 and P12, while the lowest value was 0.12 for P19. Cluster analysis led to dividing the studied hybrids into two groups; the first group included (FDR, Pharah, Bravia, Elegro, Shourouq, Ballade), and the second group included both Marah and Lamantin hybrids. The two hybrids Shourouq and Ballade were the genetically closest to each other with a genetic distance of 0.104, while Pharah hybrid was the genetically farthest from the hybrid Elegro with a genetic distance of 0.7169. These results indicate the efficiency of the ISSR primers in determining the genetic diversity among locally cultivated tomato hybrids.